Starvation Stress Causes Body Color Change and Pigment Degradation in Acyrthosiphon pisum - Wang, Xing-Xing; Chen, Zhan-Sheng; Feng, Zhu-Jun; Zhu, Jing-Yun; Zhang, Yi; Liu, Tong-Xian (Frontiers in Physiology, 2019)
The pea aphid, Acyrthosiphon pisum (Harris), shows body color shifting from red to pale under starvation in laboratory condition. These body color changes reflect aphid’s adaptation to environmental stress. To understand the color-shifting patterns, the underlying mechanism and its biological or ecological functions, we measured the process of A. pisum’s body color shifting patterns using a digital imagery and analysis system, conducted a series of biochemical experiments to determine the mechanism causing color change, and initiated biochemical and molecular analysis of energy reserves during color-shifting process. We found that the red morph of A. pisum could shift their body color to pale when starved, and changed rapidly at a certain stress threshold. Once A. pisum initiated the color-shifting process, the shifting could not be stopped or reversed even after they were re-introduced to food. We also discovered that the orange-red pigments may be responsible for the color shifting, and the shifting might be caused by the degradation of the pigments. The carbohydrate and lipid contents were correlated to the color fading in the red A. pisum, and comparing analysis revealed that these reddish pigments might be used as backup energy. Color fading reflects an energy reserves re-organization under nutritional stress for A. pisum; and surprisingly, the aphids in different body color exhibited diverse strategies in energy reserves storage and consuming.